Q. 12

# Find the sum of coefficients of two middle terms in the binomial expansion of (1 + x)2n-1

Given:

Total terms after expansion = 2n-1+1=2n

Middle term = 2n/2 = nth term

So two required middle terms are : nth & (n+1)th term

k= (n-1) & n for both terms respectively.

(1 + x)2n-1

Coefficient of nth term;

=2n-1Cn-1

Coefficient of (n+1)th term ;

= 2n-1Cn

Sum of coefficients = 2n-1Cn-1 + 2n-1Cn

= 2n-1+1Cn

=2nCn

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Finding remainder using binomial theoremFREE Class
Lecture on properties of Binomial Coefficients58 mins
Interactive Quiz on properties of Binomial Coefficients51 mins
Interactive Quiz | general & middle terms53 mins
Interactive quiz on general and middle terms of binomial theorem54 mins
Learn Binomial Theorem through Questions52 mins
Learn how to find general & middle terms41 mins
Finding coefficient of x^n in binomial expansion59 mins
Questions based on General term of Binomial Theorem58 mins
General Term of Binomial Theorem60 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses